Efektivitas Penggunaan Aplikasi Wordwall untuk Meningkatkan Hasil Belajar Ilmu Pengetahuan Sosial (IPS) Siswa Kelas VI Sekolah Dasar - Milhatun Zannah; Nurdinah Hanifah; Isrok'atun Isrok'atun (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
Based on the results of interviews with grade 6 teachers at SDN Kesambi Dalam 4 Cirebon City in social studies learning "ASEAN" material, it shows that the learning outcomes obtained by students are quite low. This research uses a quantitative type of research using quasi-experimental methods. The samples studied in this research were Class A (control) and Class B (experiment) using random sampling techniques. Research tools include validated questionnaires and multiple-choice tests whose content and level of difficulty have been reviewed by subject matter experts. Hypothesis testing using the t-test and n-gain test is the data analysis approach used. Posttest findings showed that the experimental class (80.1) was significantly different from the control class (53.7) at a significance level of 0.05 (Sig. 0.05). The resulting t-count value is also greater than t-table, namely 44.718 > 11.695. Therefore, Ha is approved while Ho is not. The results of the n-gain test increased learning outcomes by 73.78% in the experimental group compared to only 42.55% in the control group. In this way, the implementation of Wordwall has proven to be effective in improving class VI social studies learning outcomes.